Chelating Rotaxane Ligands as Fluorescent Sensors for Metal Ions. Issue 19 (6th April 2018) - Denis, Mathieu; Pancholi, Jessica; Jobe, Kajally; Watkinson, Michael; Goldup, Stephen M.
Abstract: Although metal‐ion‐binding interlocked molecules have been under intense investigation for over three decades, their application as scaffolds for the development of sensors for metal ions remains underexplored. In this work, we demonstrate the potential of simple rotaxanes as metal‐ion‐responsive ligand scaffolds through the development of a proof‐of‐concept selective sensor for Zn 2+ . Abstract : One ring to bind them : Although many mechanically chelating rotaxanes and catenanes have been reported in which donor atoms bridge the mechanical bond to bind metal ions, their use as scaffolds for the selective detection of cations remains underexplored. This simple strategy is demonstrated to be effective for the development of a fluorescent probe for metal ions.